Significance of dyspnoea as a symptom in the emergency department of the primary healthcare centre - Maksimović, Žana M; Banjac, Nada; Čović, Miloš (Scripta Medica, 2020)
Background/Aim: Dyspnoea represents a subjective feeling of laboured breathing of different intensity. The aim of this study was to determine how often patients come with dyspnoea to a local Emergency Department of the Primary Healthcare Centre (EDPHC) and to analyse the assumed aetiology, diagnostics and therapy of the dyspnoeic patients. Methods: The records of the EDPHC of the City of Banja Luka for the period between 1 October 2019 to 31 December 2019 of all patients older than 15 years of age that have reported laboured breathing were identified and analysed. Following parameters were recorded: age, gender, diagnostics performed, administered therapy, whether the patient was examined in the field or in the ambulance, as well as whether the patient was referred to a hospital (Cardiology, Pulmonology or another department) or not. Results: Laboured breathing was reported by 665 patients. Out of this number, 108 patients were examined by their family doctor, 407 patients in EDPHC ambulance and 150 patients in the field. The average age of the patient was 61.03 ± 19.17, with an equal distribution in males and females. The aetiology of dyspnoea was cardiac and pulmonary in one-third of patients each, whereas the diagnosis in the other patients was versatile, from anxiety disorders, musculoskeletal diseases and active malignancy to unspecified chest pain that could not receive a definitive diagnosis. One half of the patients (N = 261 or 46.86 %) was completely taken care of in the ambulance or in the field, 199 (35.73 %) patients were sent to a cardiologist, 87 (15.62 %) to a pulmonologist and 10 (1.80 %) of patients to another specialist. Referral to hospital was registered more often in men (χ 2 = 9.195, p = 0.027), elderly (χ 2 = 53.29, p < 0.001), people with lower peripheral oxygen saturation (SpO 2 ) (χ 2 = 120.61, p < 0.001) and people with significant deviation of normal blood pressure values (χ 2 =120.61, p < 0.001). Conclusion: Dyspnoea can be caused by an array of different diseases and more than one diagnostic method is necessary to confirm/exclude any of the most common causes of dyspnoea. A broader diagnostical palette in ED would be preferred for purposes of ascertaining a timely diagnosis.